SETTLEMENT OF CONSUMER COMPENSATION CLAIMS AGAINST BUSINESS ACTORS FROM EXPIRED FOOD - Situmorang, Nixon; Cavenagh, Thomas (SYNTIFIC, 2025)
Background. Due to serious concerns about illegal business practices in Indonesia's food manufacturing sector, the government passed Law Number 8 of 1999 on Consumer Protection (UUPK). This law seeks to protect consumer rights and promote moral business practices, especially when it comes to food product marketing. Despite these regulations, violations still occur, often resulting in consumer harm. One such instance is illustrated by Criminal Case Number 747/Pid.B/2020/PN.Bgl, where the defendant was found guilty of selling expired food, highlighting the ongoing risks faced by consumers. This study investigates the legal mechanisms for resolving disputes between consumers and business actors, with a focus on the legal responsibilities of businesses that violate consumer protection laws. Research Method. This study used a normative legal research method. The analysis is based on statutory regulations and case law, particularly Article 1365 of the Indonesian Civil Code regarding unlawful acts. Findings. Selling expired food constitutes an unlawful act under Indonesian law and causes material and moral losses to consumers. Business actors are not only subject to criminal penalties but are also obligated to provide compensation for damages. Conclusion. Stronger enforcement of consumer protection laws and increased awareness among business actors are essential to prevent future violations. Legal remedies must be applied consistently to uphold justice and consumer rights.